ANALYSIS OF OPERATIONAL MANAGEMENT OF ACADEMIC INSTITUTIONS (Case Study on the STIAMI Institute) - Aryani Aryani; Malviyola el barqa; Roviuddin Roviuddin; Safuan Safuan (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Operational management itself is the main management function in a company. Operations management is growing rapidly due to technological advancements and the emergence of new innovations implemented in business practices. Currently, many companies have glanced at and made operations management a strategic tool in competing between companies. Operational management is needed to give birth to new innovations and changes for the better. Because along with the times, the industry is getting more advanced so that companies are required to present the best quality in the products or services produced, but do not forget the impact on the surrounding environment from all company activities. This study aims to analyze operational management in academic institutions. The focus of this research is to identify strengths, weaknesses, opportunities, and threats in operational management and provide recommendations for improving operational efficiency and effectiveness. The research methods used include interviews, surveys, and document analysis. The results of the study show that effective operational management can improve the quality of education services and operational efficiency.